Inhibition of the symbiotic fungus of leaf-cutting ants by coumarins - Godoy,Marizete F. P. (2005)
Leaf-cutting ants are known to be a serious pest for agriculture due to the high amounts of vegetal matter from crops used by them in order to cultivate a symbiotic fungus on which they rely for food and enzymes. The mutualism between the fungus and the ants is a point to be explored when alternative methods of control are being thought of. Considering that some plants are naturally resistant to phytophagous insects, some natural products (secondary metabolites) should be evaluated with respect to their insecticide and/or fungicide properties. In this paper we isolated eight coumarins from four different plant species and we determined their effect on the development of the symbiotic fungus of the leaf-cutting ant Atta sexdens. With the exception of clausarin, all the other coumarins were inhibitory from 64 µg mL-1 through 80 µg mL-1 and xanthyletin inhibited the fungus at 25 µg mL-1